PENGARUH KECERDASAN EMOSIONAL DAN SPIRITUAL TERHADAP KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA DAN KINERJA MANAGER (Studi Kasus pada Bank Syariah Indonesia di Kota Malang) - Winda Armeinita Wulandari; Dwiyani Sudaryanti; M Cholid Mawardi (El-Aswaq, 2020)
This study was to determine the effect of the emotional, spiritual intelligence on transformasional leadership, job satisfaction and manager performance at Indonesian Islamic Banks in the City of Malang. This type of research in quantitative research. In this study, the samples taken were employees of 3 (three) Indonesian Islamic Banks in the City of Malang, namely BSI-KCP Malang-Lawang, BSI-KCP Malang-Suhat, BSI-KCP Malang-Pasbes, totaling 40 people. Taking the number of samples using saturated sampling. The analytical tool used is  multiple linier regression analysis using the SPSS 16 analysis tool. The result show that emotional intelligence variable (X1) have a negative and partially insignificant effect on transformasional leadersip (Y1), emotional intellegence (X1) has a negative and not significant effect. Partially significant on the variable job satisfaction (Y2), emotional intelligence (X1) has a positive and partially significant effect on the manager’s performance variable (Y3). And the spiritual intelligence variable (X2) both have a positive and partially significant effect on transformational leadersip (Y1) and manager performance (Y3). While the spiritual intelligence variable (X2) has a negative and partially insignificant effect on job satisfaction variable (Y2).